Personally Speaking : Experience as Evidence in Academic Discourse - Spigelman, Candace, 1947- (Book collections on Project MUSE., 2004)
Responding to contemporary discussion about using personal accounts in academic writing, Personally Speaking: Experience as Evidence in Academic Discourse draws on classical and current rhetorical theory, feminist theory, and relevant examples from both published writers and first-year writing students to illustrate the advantages of blending experiential and academic perspectives. Candace Spigelman examines how merging personal and scholarly worldviews produces useful contradictions and contributes to a more a complex understanding in academic writing. This rhetorical move allows for greate.